Activation of ALDH2 with Low Concentration of Ethanol Attenuates Myocardial Ischemia/Reperfusion Injury in Diabetes Rat Model. (18th October 2016) - Kang, Pin-Fang; Wu, Wen-Juan; Tang, Yang; Xuan, Ling; Guan, Su-Dong; Tang, Bi; Zhang, Heng; Gao, Qin; Wang, Hong-Ju
Abstract : The aim of this paper is to observe the change of mitochondrial aldehyde dehydrogenase 2 (ALDH2) when diabetes mellitus (DM) rat heart was subjected to ischemia/reperfusion (I/R) intervention and analyze its underlying mechanisms. DM rat hearts were subjected to 30 min regional ischemia and 120 min reperfusion in vitro and pretreated with ALDH2 activator ethanol (EtOH); cardiomyocyte in high glucose (HG) condition was pretreated with ALDH2 activator Alda-1. In control I/R group, myocardial tissue structure collapse appeared. Compared with control I/R group, left ventricular parameters, SOD activity, the level of Bcl-2/Bax mRNA, ALDH2 mRNA, and protein expressions were decreased and LDH and MDA contents were increased, meanwhile the aggravation of myocardial structure injury in DM I/R group. When DM I/R rats were pretreated with EtOH, left ventricular parameters, SOD, Bcl-2/Bax, and ALDH2 expression were increased; LDH, MDA, and myocardial structure injury were attenuated. Compared with DM + EtOH I/R group, cyanamide (ALDH2 nonspecific blocker), atractyloside (mitoPTP opener), and wortmannin (PI3K inhibitor) groups all decreased left ventricular parameters, SOD, Bcl-2/Bax, and ALDH2 and increased LDH, MDA, and myocardial injury. When cardiomyocyte was under HG condition, CCK-8 activity and ALDH2 protein expression were decreased. Alda-1 increased CCK-8 and ALDH2. Our findings suggested enhanced ALDH2 expression in diabetic I/R rats played the cardioprotective role, maybe through activating PI3K and inhibiting mitoPTP opening.